Program TARP jako narzędzie bezpośredniego wsparcia finansowego banków w okresie kryzysu - Karaś, Piotr (The Troubled Asset Relief Program as an Instrument of Direct Financial Support to Banks in the Crisis, 2009)
On October 3, 2008 Emergency Economic Stabilization Act of 2008 was signed into law in the USA. On the strength of the Act the Troubled Asset Relief Program was established. An essential part of the TARP forms the basis for providing public funds to help American financial institutions (notably banks) gain additional capital and restore the flow of credit to the economy. The aim of this article is to present three particular programs established under the TARP (Capital Purchase Program, Asset Guarantee Program, and Targeted Investment Program) that are addressed directly and exclusively to banks.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 626-633